PENGARUH KUALITAS PRODUK DAN KERAGAMAN PRODUK TERHADAP KEPUASAN KONSUMEN DENGAN LOYALITAS KONSUMEN SEBAGAI VARIABEL INTERVENING PADA TOKO PAKAIAN Lva Boutique ASEMBAGUS SITUBONDO - Mahendra, Jaka; Arief, Mohammad Yahya; Ariyantiningsih, Febri (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
This study aims to determine the Effect of Product Quality and Product Diversity on Consumer Satisfaction with Consumer Loyalty as an Intervening Variable at “Lva Boutique “Clothing Store in Asembagus, Situbondo. with Consumer Loyalty as an intervening variable. The population in this study were all visitors to the Lva Boutique AsembagusSitubondo Clothing Store. The sampling method is random (simple probability sampling) without regard to the strata in the population in this research. Data analysis and hypothesis testing in research using the Structural equation model-partial Least square (PLS-SEM). The results of testing the hypothesis of direct influence using the smart PLS 3.0 application show that product quality significantly affects consumer loyalty. Product diversity has a significant positive effect on consumer loyalty. Product quality has a significant positive effect on customer satisfaction. Diversity has a positive but insignificant effect on consumer satisfaction. Customer satisfaction has a significant positive effect on customer loyalty. Product quality has a significant positive effect on customer loyalty through customer satisfaction. Product diversity has a significant positive effect on customer satisfaction through customer loyalty.